Analisis Faktor-Faktor yang Mempengaruhi Penerapan SAK-EMKM pada UMKM Anggota CU Prima Danarta - Rr. Puruwita Wardani; Susanna Hartanto (JURNAL ONLINE INSAN AKUNTAN, 2022)
This study examines the factors (age of business, education level, educational background, and socialization of SAK EMKM) that influence the implementation of SAK EMKM for members of CU Prima Danarta who have business. This study was conducted during the Covid-19 pandemic. The data were obtained from questionnaires distributed to members of CU Prima Danarta who have businesses and 52 questionnaires could be processed. The theory of planned behavior is used as an approach in this study in explaining the factors that influence the implementation of SAK EMKM. The results of this study are the age of business has a negative effect on the implementation of SAK EMKM, socialization of SAK EMKM has a positive effect on the implementation of SAK EMKM, education level has no effect on the implementation of SAK EMKM, and also educational background has no effect on the implementation of SAK EMKM. Socialization from the IAI and academicians is needed to support the implementation of SAK EMKM for SME members of CU Prima Danarta.